Effects of Health-Related Fitness Model Implementation in Physical Education on Active Lifestyle of Vocational High School Students - Sheila Dwi Loviani; Amung Ma’mun; Nurlan Kusmaedi (Universitas Pendidikan Indonesia, 2022)
This study aimed to determine the effect of implementing a health-related fitness model on vocational high school students' physical and physical activity improvements. The method used in this study was the experimental method with a randomized control group pre-test post-test design. The sampling method used a random cluster sampling technique by selecting two classes. One class was assigned as the experimental group, while another class was assigned as the control group. Each class consisted of 33 students aged 16-17 years. The instruments used in this study were the physical fitness test instrument and the student physical activity test instrument. The data analysis employed SPSS 20 application. The result showed a relationship between student understanding of health-related fitness, student physical fitness, and their active lifestyle. This study provides information that understanding health-related fitness has a significant influence on physical fitness and active lifestyle. The implications of this study emphasize that a good understanding of health-related fitness can have a significant impact on oneself, friends, relatives, family, and society.